PEMENUHAN HAK DAN PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN YANG MENGALAMI KELEBIHAN KAPASITAS (Studi Kasus Lembaga Pemasyarakan Klas IIA Tembilahan) - Islami, Lielyana Adenur; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Correctional institution as a part of the criminal justice system has responsibility to delegate the realization of the ultimate goal of criminal justice system, namely the rehabilitation and resocialization for the lawbreakers. See the goals that need to be achieved he the fulfillment of the rights of convicts being a thing that is inevitable. But the problem that arise these time almost all the correctional institution in Indonesia are experiencing overcapacity, so that the rights of convicts are often not fulfilled and the fostering enforcement does not run properly, as well as occur in class IIA correctional institution of Tembilahan.In accordance with the above description, the writer is interested in conducting research with the title, The fulfillment of rights and the fostering of convicts in correctional institution that are experiencing overcapacity (study case in class IIA correctional institution of Tembilahan) this thesis aims to know the implementation of the fulfillment of the rights and the fostering of convicts in correctional institution that are experiencing overcapacity and to know the efforts that must be made so the fulfillment of rights and the fostering of convicts is not hampered because overcapacity in correctional institution.In this thesis the writer is using sociological research method with descriptive writing that gives an overview in detail dan clearly about the fulfillment of rights and the fostering of convicts in correctional institution that are experiencing overcapacity. The results of the research conducted by qualitative analysis and by using deductive method.From the results it can be concluded that the implementation of the fulfillment of rights and the fostering of convicts have not been going well due to overcapacity issue. The efforts for the problem are being made that is doing the transfer of convicts, correctional institution improvements, adding the budget funds, acceleration of granting remission, assimilation, parole and furlough towards free and need an understanding of the functions of the correctional institution at establishments within the ranks of the criminal justice system and the need to build a specific correctional institutions for narcotics in every province due to overcapacity domination by the convict of narcotic cases.Keywords : The Fulfillment of The Rights, Fostering, Correctional Institutions